A new time-dependent trading strategy for securitized real estate and equity indices - Hui, Eddie C. M.; Chan, Ka Kwan Kevin (International Journal of Strategic Property Management, 2018)
The “buy-and-hold” strategy based on the EMH has been adopted by many investors for long. However, the global financial crisis in 2008 caused more doubt to be cast on EMH. Therefore, many scholars have attempted to create a trading strategy which can outperform the “buy-and-hold” strategy. In this study, we use the Shiryaev-Zhou index to derive a new generalized time-dependent strategy of which the moving-window size can be changed to see how the moving-window size affects the resulting profit of our strategy. We test our strategy on the securitized real estate and general equity indices of six economies, and find the optimal moving-window size for our strategy on each stock index. The results show that when the optimal moving-window size is used, our strategy outperforms the “buy-and-hold” strategy for most cases. Furthermore, during stock market downturns, it’s advisable to adopt our strategy, preferably with larger moving-window sizes, to prevent losses when the stock prices fall rapidly. However, during long periods of booms, it’s better to adhere to the “buy-and-hold” strategy. This implies that we should switch strategies when market fundamentals changes significantly. Property practitioners can also apply this strategy for a better portfolio management to increase their profit.First published online 29 September 2017